2015
DOI: 10.1007/s00181-015-0944-9
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and growth in Lebanon: new evidence from bootstrap simulation and rolling causality approaches

Abstract: A multivariate model incorporating tourist arrivals, real output, and the real exchange rate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 56 publications
1
49
0
Order By: Relevance
“…Specifically, Ghali (1976) was the first to investigate the nexus between tourism and economic growth from an empirical perspective using the ordinary least square method, and Balaguer and Cantavella-Jordá (2002) were pioneers in examiningthe validity of the TLG hypothesis. The results of this line of research are sensitive to the sample period, model specification, variablesselected,frequency of observations, methodological approachapplied and country/countries involved, althoughthe majority of studies support the TLG hypothesis (e.g., Brida et al, 2008;Gunduz and Hatemi-J, 2005;Nowak and Sahli, 2007;Tang and Abosedra, 2016;Tang and Tan, 2015).However, a number ofstudies (Lee, 2012;Oh, 2005;Payne and Mervar, 2010;Tang and Jang, 2009)have identified the reverse effect, that economic development boosts tourism expansion. This hypothesis, called the growth-led tourism hypothesis, postulates that the sustained economic growth of a country facilitates the development of the tourism sector in that country.As resources become available for tourism infrastructure, the positive economic climate encourages the proliferation of tourism activities, and international tourists are also attracted by the country's economic vitality.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Specifically, Ghali (1976) was the first to investigate the nexus between tourism and economic growth from an empirical perspective using the ordinary least square method, and Balaguer and Cantavella-Jordá (2002) were pioneers in examiningthe validity of the TLG hypothesis. The results of this line of research are sensitive to the sample period, model specification, variablesselected,frequency of observations, methodological approachapplied and country/countries involved, althoughthe majority of studies support the TLG hypothesis (e.g., Brida et al, 2008;Gunduz and Hatemi-J, 2005;Nowak and Sahli, 2007;Tang and Abosedra, 2016;Tang and Tan, 2015).However, a number ofstudies (Lee, 2012;Oh, 2005;Payne and Mervar, 2010;Tang and Jang, 2009)have identified the reverse effect, that economic development boosts tourism expansion. This hypothesis, called the growth-led tourism hypothesis, postulates that the sustained economic growth of a country facilitates the development of the tourism sector in that country.As resources become available for tourism infrastructure, the positive economic climate encourages the proliferation of tourism activities, and international tourists are also attracted by the country's economic vitality.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The sample period spans from 1990Q1 to 2015Q4, with a total of 104 quarterly observations. Three key variables havetraditionally been employed in the tourism economics literature to measure the volume of tourism flows: the total number of international tourist arrivals (Gunduz and Hatemi-J, 2005;Katircioglu, 2009;Kim et al, 2006;Tang and Abosedra, 2016), international tourism receipts (Arslanturk et al, 2011;Balaguer and Cantavella-Jordá, 2002;Chen and Chiou-Wei, 2009;Ridderstaat et al, 2014), and international tourism expenditures (Aslan, 2016;Cárdenas-García et al, 2015;Song et al, 2010;Tugcu, 2014). However, a major drawback of these common tourismactivity indicators is that such indicators only show a partial connection to economic growth.…”
Section: Data Descriptionmentioning
confidence: 99%
“…(2014), Kumar (2014), Tang and Tan (2015), Tang and Abosedra (2016) are among the studies that found evidence of bi-directional causality between tourism and economic growth regardless of model specification (i.e. bi-variate, tri-variate or multivariate models).…”
Section: Studies On the Nexus Of Tourism And Economic Growthmentioning
confidence: 99%
“…Tang and Tan (2015) 1975-2011 (A) Malaysia Johansen-Juselius; Granger causality -VECM EG; TOUR; PS; GNS EG  TOUR 40. Tang and Abosedra (2016) 1995 - Katircioğlu (2014a) 1960-2010 (A) Turkey ARDL; IRF; VD EG; EC; TOUR; CO2 TOUR  EC 44. Katircioğlu (2014b) 1971-2010 (A) Singapore Multiple break cointegration test; VD; Granger causality -VECM EG; EC; TOUR; CO2 TOUR  EC 45.…”
mentioning
confidence: 99%
“…Simultaneously, Egypt needs to improve economic growth for stimulating the influence of the tourism industry. Tang and Abosedra (2016) used multivariate modeling to analyze the causal connection between tourism and economic progress in Lebanon using the bootstrap causality method. They also used Granger causality with a rolling window and observed the validity of the TLGH for the Lebanese economy.…”
Section: Literature Surveymentioning
confidence: 99%